2021
DOI: 10.1039/d0na00828a
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid magnetic nanoparticles as efficient nanoheaters in biomedical applications

Abstract: In this minireview we discuss and provide a perspective on the novel systems, the synthesis routes and the interface-mediated properties that determine the heating efficiency of hybrid magnetic nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 236 publications
(354 reference statements)
0
51
0
Order By: Relevance
“…In particular, significant advances have been made in soft/hard bi-magnetic nanoparticles for hyperthermia and other biomedical applications (e.g. magnetic resonance imaging (MRI), on-demand drug release and target drug delivery) [4][5][6][7][8]. Moreover, the manipulation of a bi-magnetic core/shell nanoarchitecture is a powerful tool for obtaining new functionalities in a single nanoscale object [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, significant advances have been made in soft/hard bi-magnetic nanoparticles for hyperthermia and other biomedical applications (e.g. magnetic resonance imaging (MRI), on-demand drug release and target drug delivery) [4][5][6][7][8]. Moreover, the manipulation of a bi-magnetic core/shell nanoarchitecture is a powerful tool for obtaining new functionalities in a single nanoscale object [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…9 nm (i.e., in the same superparamagnetic regime as those in [22]) with a maximum of only~100 W/g (concentration below 5 mg/mL) [25]. With regards to the improvement in SLP due to an interphase exchange mechanisms [26], an example shows synergistic effects (SLP~500 W/g) in soft MnFe 2 O 4 and hard CoFe 2 O 4 bimagnetic clusters when compared with the homomagnetic 9 nm counterparts (~100 and~200 W/g for Mn-and Co-ferrite, respectively) [27]. Such SLP values are similar to many others in the literature [28][29][30][31][32][33].…”
Section: Comparison With Other Core-shell Systemsmentioning
confidence: 99%
“…Recently, MNWs became the center of the research in nanobarcoding because of the revealed potential for making the next generation of nanobarcodes and/or biolabels [ 23 , 24 , 25 , 26 ], driven by the fact that the MNWs can be remotely and selectively detected [ 27 , 28 , 29 ]. Moreover, the MNWs are dominantly fabricated using electrodeposition techniques that are cheap, fast, and scalable for mass production [ 30 , 31 , 32 , 33 ].…”
Section: Why Magnetic Nanowires For Nanobarcodes?mentioning
confidence: 99%